PENGARUH LITERASI KEUANGAN, PENDAPATAN, DAN SIKAP KEUANGAN TERHADAP PERILAKU MANAJEMEN KEUANGAN PADA PELAKU USAHA MIKRO, KECIL DAN MENENGAH DI KELURAHAN PALEDANG KOTA BOGOR - Aninda Zahra Kurniawan (2020)
This research has purpose to find the effect of financial literacy, income, and financial attitude on financial management behavior in micro, small and medium enterprises in Paledang urban village the city of Bogor. the population in this study were all micro, small and medium enterprises in Paledang urban village the city of Bogor, amounting to 59 businesses. the sample size used was 59 respondents with a probability sampling and cluster sampling method. The data collection is used through questionnaires. The analysis technique used is the PLS (Partial Least Square) analysis method. The results of this study indicate that (1) financial literacy have a significant effect on financial management behavior, (2) Income does not affect on financial management behavior, (3) financial attitude have a significant effect on financial management behavior Keyword : Financial literacy, income, financial attitude and financial management behavior